Siglec15 in blood system diseases: from bench to bedside - Fan, Yujia; Sun, Liangliang; He, Juan; Chen, Yuetong; Ma, Hongli; Ding, Haitao (Frontiers in Immunology, 2024)
Inhibiting the PD-1/PD-L1 pathway using immunomodulators has demonstrated promising outcomes in clinics. Immunomodulators can effectively target immune checkpoints with a strong preference for the tumor microenvironment (TME). Besides, immunomodulators specifically target the recently discovered inhibitory immune checkpoint, sialic acid-binding immunoglobulin-like lectin (Siglec-15). Distinctive in its molecular composition, Siglec-15 has a unique molecular composition and been shown to be highly prevalent in numerous solid tumor tissues and tumor-associated macrophages (TAMs) in human subjects. Notably, Siglec-15 is up-regulated across various cancer types. As a result, Siglec-15 has attracted significant attention due to its exclusive nature concerning PD-L1 expression, suggesting its role in immune evasion in patients lacking PD-L1. Siglec-15 predominantly appears in certain populations and can promote tumor development by repressing T lymphocyte activation and proliferation, thereby facilitating tumor cell immune escape. Furthermore, Siglec-15 is implicated in osteoclast differentiation and bone remodeling, indicating that it is a promising target for next-generation cancer immunotherapies. Additionally, Siglec-15 can modulate immune responses to microbial infections. The current treatment strategies for hematological conditions predominantly include conventional intensive chemotherapy and transplantation methods. However, emerging immunotherapeutic approaches are increasingly recognized for their overall effectiveness, indicating that specific molecular targets should be identified. The expression of Siglec-15 within tumor cells may indicate a novel pathway for treating hematological malignancies. In this study, the biological attributes, expression patterns, and pathogenic mechanisms of Siglec-15 across various diseases were reviewed. The role of Siglec-15 in the pathogenesis and laboratory diagnosis of hematological disorders was also evaluated.